Precautionary savings by natives and immigrants in Germany - Matloob Piracha; Yu Zhu (Institute for the Study of Labor (IZA), 2007)
This paper analyses the savings behaviour of natives and immigrants in Germany. It is argued that uncertainty about future income and legal status (in case of immigrants) is a key component in the determination of the level of precautionary savings. Using the German Socio-economic Panel data it is shown that, although immigrants have lower levels of savings and are less likely to have regular savings than natives, the gap is significantly narrowed once we take loan repayments and remittances into account. Moreover, we find that marginal propensity to save for immigrants is about 40% higher than that for natives. We then exploit a natural experiment arising from a change in nationality law in Germany in 2000 to estimate the importance of precautionary savings. Using a difference-in-differences approach, we find that the easing of the requirements for naturalization has caused significant reductions of savings and remittances for immigrants as a whole, in the magnitude of 13% and 29% respectively, comparing to the pre-reform period. Our parametric specification shows that the introduction of the new nationality law reduces the gap between natives and immigrants in marginal propensity to save by 40% to 65%, depending on the measure of savings used. These findings suggest that much of the differences in terms of the savings behaviour between natives and immigrants are driven by the precautionary savings arising from the uncertainties about future income and legal status rather than cultural differences.
Keywords: 330; Sparen; Kassenhaltungsansatz; Migranten; Rücküberweisung (Migranten); Deutschland